Lithium fluoride ceramic target material as well as preparation method and application thereof

Through the combination of pressure-free sintering and HIP post-treatment, the problem of low density of lithium fluoride ceramic targets in the prior art is solved, and high density and excellent comprehensive performance are achieved. It is suitable for lithium-ion batteries and optical materials. .

CN119430944AActive Publication Date: 2025-02-14KONFOONG MATERIALS INTERNATIONAL CO LTD

Patent Information

Application Number
CN202411742309.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to prepare lithium fluoride ceramic targets with high density, resulting in poor application performance in lithium-ion batteries and optical materials.

Method used

Using a sintering method that combines pressure-free sintering and HIP post-treatment, the phase composition and display of the material are adjusted by pre-firing the blank in a pressure-free high-temperature environment and reducing or eliminating defects such as residual pores inside the material during HIP post-treatment. Microstructure.

Benefits of technology

It significantly improves the density of lithium fluoride ceramic targets, with a density of 97%-99%, and improves the comprehensive performance of the materials. It is suitable for lithium-ion batteries and optical materials fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430944A_ABST
    Figure CN119430944A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium fluoride ceramic target material and a preparation method and application thereof, and the preparation method comprises the following steps: uniformly mixing lithium fluoride and a binder solution to obtain a precursor, carrying out mold pressing or dry pressing molding on the precursor, and then carrying out cold isostatic pressing molding to obtain a biscuit; carrying out pressureless sintering on the biscuit to obtain a sintered body, and carrying out HIP post-treatment on the sintered body to obtain a lithium fluoride ceramic target material; according to the method, under the condition that no sintering aid is introduced, the defects such as pores in the grain boundary area of the sintered body are removed by adding the HIP post-treatment process, and the lithium fluoride ceramic target material with relatively high density is obtained. The high-density lithium fluoride ceramic target material can be obtained by adopting a mode of combining pressureless sintering and HIP post-treatment, and the density of the lithium fluoride ceramic target material prepared by the method is 97%-99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluoride ceramics, and in particular to a lithium fluoride ceramic target material and a preparation method and application thereof. Background Art

[0002] Fluoride and oxide ceramic targets are widely used in high-tech fields. Fluoride targets, such as magnesium fluoride and calcium fluoride, excel in optical lenses and window materials due to their high refractive index and low dispersion characteristics. Oxide targets, such as aluminum oxide and zirconium oxide, are often used to manufacture cutting tools and wear-resistant coatings due to their high hardness and wear resistance. In addition, these ceramic targets also play an important role in the semiconductor, photovoltaic industry, and data storage devices, and are used to prepare thin films and coatings to improve product performance and durability. For the study of ceramic target preparation methods, the current prior art has disclosed methods for preparing oxide ceramics using pressureless sintering, vacuum hot pressing sintering, and cold sintering technology. Among them, the use of pressureless sintering for the preparation of oxide ceramics can greatly reduce production costs, but it is difficult to make the ceramics completely densified by relying solely on temperature as a sintering aid, and there are pore defects in the grain boundary area; if hot pressing sintering is used, the use of graphite molds is likely to cause carbon contamination to the sample, and because hot pressing sintering is unidirectional pressure, the uneven pressure distribution in the blank during sintering can easily cause preferential orientation of the microstructure.

[0003] There are two types of hot isostatic pressing (HIP): encapsulated and non-encapsulated. Encapsulated hot isostatic pressing refers to placing metal powder or compact in a encapsulated material and vacuum sealing it with the help of inert gas (N 2 , Ar, etc.), and assisted by high temperature, to finally achieve densification. Unencased hot isostatic pressing is to put a sintered body with a relative density greater than 93% and no open pores into a high-pressure container of a hot isostatic press, and densify the material by the combined action of high temperature and high pressure. Unencased hot isostatic pressing is also called HIP post-treatment, which is the method used in the present invention.

[0004] The higher the density of the ceramic target, the fewer pores inside it and the more uniform the microstructure, which has an important impact on the performance of the target. High-density ceramic targets have the following advantages: improved film quality, enhanced mechanical strength, improved electrical properties, improved thermal stability, reduced raw material waste, enhanced chemical stability, improved wear resistance, and improved optical properties. In optical applications, high-density targets can provide more uniform films, thereby improving optical properties such as transmittance and reflectivity.

[0005] Therefore, improving the density of the target material is of great significance for improving the performance of the film, extending the service life of the target material and reducing the production cost. In practical applications, the density of the target material can be improved by optimizing the sintering process, such as controlling the sintering temperature, time and atmosphere. In addition, the use of high-purity raw materials, fine grinding and screening of powders, premixing and drying are also important factors in improving the quality of the target material.

[0006] With the development of lithium-ion battery technology, the beneficial properties of lithium fluoride materials for batteries have received more and more widespread attention. Introducing lithium fluoride into the interface between the electrode and the solid electrolyte can significantly improve the ion conduction at the interface, thereby improving the performance of lithium-ion batteries. Therefore, it is urgent to develop a lithium fluoride ceramic target with a higher density, which is conducive to the formation of a complete lithium fluoride film with uniform thickness during the introduction of lithium fluoride into lithium-ion batteries.

[0007] In the preparation process of fluoride ceramic targets, common methods include sintering aid assisted pressureless sintering, vacuum hot pressing sintering, etc. However, the relative density of LiF ceramic targets prepared by the above methods is at most about 94%, and the density is relatively low. Therefore, how to provide a lithium fluoride ceramic target with high density and a preparation method has become a problem that needs to be solved urgently. Summary of the invention

[0008] In order to solve the above technical problems, the purpose of the present invention is to provide a lithium fluoride ceramic target material and a preparation method and use thereof. The preparation method of the lithium fluoride ceramic target material of the present invention does not require the introduction of any sintering aid. The green blank is first pre-fired in a pressureless high-temperature environment, and then HIP post-treatment can effectively reduce or eliminate defects such as residual pores inside the material, adjust the phase composition and microstructure of the material, thereby improving the density of the lithium fluoride ceramic material and enhancing the comprehensive performance of the material.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a lithium fluoride ceramic target, the preparation method comprising the following steps:

[0011] The lithium fluoride and the binder solution are uniformly mixed to obtain a precursor, the precursor is molded or dry pressed, and then cold isostatically pressed to obtain a green blank; the green blank is pressurelessly sintered to obtain a sintered body, and the sintered body is post-treated with HIP to obtain a lithium fluoride ceramic target.

[0012] The present invention obtains a lithium fluoride ceramic target with high density by adding a HIP post-treatment process to remove defects such as visible pores in the grain boundary area of ​​the sintered body without introducing any sintering aids. The preparation method used in the prior art is generally a hot pressing sintering step. This process has carburization and reduces the purity of the material. In addition, this sintering method has high requirements on equipment and requires higher manufacturing costs. The present invention adopts a sintering method that combines pressureless sintering with HIP post-treatment. The pressureless sintering has relatively simple requirements on equipment and process, and has a low production cost. At the same time, a sintered body with a certain organizational structure can be prepared. The subsequent HIP heat treatment process can effectively eliminate open pores, and a high-density lithium fluoride ceramic target can be obtained.

[0013] The HIP post-treatment adopted in the present invention is hot isostatic pressing sintering without a jacket. Compared with traditional hot isostatic pressing sintering, this treatment method reduces the manufacturing cost and process difficulty.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] Preferably, the temperature of the HIP post-treatment is 600°C-750°C, for example, 600°C, 650°C, 700°C or 750°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0016] The present invention further controls the temperature of HIP post-treatment to be 600°C-750°C. The temperature of HIP post-treatment will affect the density of lithium fluoride ceramic target and needs to be coordinated with pressureless sintering. The melting point of lithium fluoride is 845°C. If the temperature of HIP post-treatment is too high, the ceramic material may be over-sintered and abnormal grain growth may occur. In addition, the high temperature environment has higher requirements for equipment, which may lead to increased energy consumption and thus increase production costs. If the temperature of HIP post-treatment is too low, the bonding phase of the pre-fired ceramic particles may not be fully diffused, resulting in uneven microstructure and decreased ceramic performance.

[0017] Preferably, the pressure of the HIP post-treatment is 70 MPa-100 MPa, for example, 70 MPa, 75 MPa, 80 MPa, 85 MPa, 90 MPa, 95 MPa or 100 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] Preferably, the HIP post-treatment time is 1 h-5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the lithium fluoride is dried and sieved before mixing.

[0020] Preferably, the drying temperature is 50°C-90°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the drying time is 2h-20h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the average particle size of the lithium fluoride obtained after the screening treatment is 50 nm-100 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] The present invention further regulates the average particle size of the raw material lithium fluoride to be 50nm-100nm, so as to obtain a uniform and high-density lithium fluoride ceramic target. If a lithium fluoride material with an average particle size lower than 50nm is selected, excessively fine particles are prone to adsorb a large amount of gas, hindering contact between particles and thus hindering sintering; if a lithium fluoride material with an average particle size higher than 100nm is selected, the diffusion path of the coarse particles is longer and the atomic diffusion rate is slower, requiring a higher sintering temperature and a longer sintering time to achieve the same sintering effect.

[0024] Preferably, the concentration of the binder solution is 1wt%-5wt%, for example, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the binder solution includes PVA solution or ethanol.

[0026] The purpose of using a binder in the present invention is to enable lithium fluoride to be quickly molded.

[0027] Preferably, the mass fraction of the binder solution in the precursor is 0.5wt%-5wt%, for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the cold isostatic pressing pressure is 50 MPa-250 MPa, for example, it can be 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa, 220 MPa, 230 MPa, 240 MPa or 250 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In the present invention, the pressure during molding or dry pressing is adjusted according to the size of the mold or the size of the sample. The purpose of this step is to mold the powder sample and reduce the gaps between the powder particles.

[0030] Preferably, the cold isostatic pressing time is 30 min-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the pressureless sintering temperature is 500°C-700°C, for example, 500°C, 550°C, 600°C, 650°C or 700°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] The present invention further controls the temperature range of pressureless sintering to be 500℃-700℃. If the temperature of pressureless sintering is too high, the growth rate of grains will increase significantly, and the residual gas (such as moisture, organic volatiles, etc.) in the raw materials will be released by pyrolysis and cannot be discharged in time. As the grain boundaries migrate, they are wrapped inside the grains, resulting in a decrease in the densification degree of the material and deterioration of performance. If the temperature of pressureless sintering is too low, the energy obtained by the powder particles is insufficient, and it is difficult to overcome the potential barrier between particles, resulting in insufficient sintering driving force. This will affect the diffusion and rearrangement between particles, hindering the sintering densification process and making it difficult to form a compact structure.

[0033] Preferably, the heating rate of the pressureless sintering is 1°C / min-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the pressureless sintering time is 1 h-5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0036] The lithium fluoride is dried at 50° C.-90° C. for 2 h-20 h, and then sieved to obtain lithium fluoride with an average particle size of 50 nm-100 nm.

[0037] The precursor is obtained by uniformly mixing lithium fluoride with an average particle size of 50nm-100nm and a PVA solution with a concentration of 1wt%-5wt%, wherein the mass fraction of the binder solution in the precursor is 0.5wt%-5wt%; the precursor is molded or dry-pressed, and then cold isostatically pressed at 50MPa-250MPa for 30min-60min to obtain a green blank.

[0038] The green blank is heated to 500-700°C at a heating rate of 1°C / min-10°C / min and pressurelessly sintered for 1h-5h to obtain a sintered body. The sintered body is post-treated by HIP at 600-750°C and 70MPa-100MPa for 1h-5h to obtain a lithium fluoride ceramic target with a density of 97%-99%.

[0039] In a second aspect, the present invention provides a lithium fluoride ceramic target material, which is prepared according to the preparation method of the lithium fluoride ceramic target material described in the first aspect, and has a density of 97%-99%.

[0040] The density of the lithium fluoride ceramic target prepared by the present invention is above 97.0%, which significantly improves the density of the lithium fluoride ceramic target. For example, it can be 97.0%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98.0%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9% or 99%; but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0041] In a third aspect, the present invention provides a use of a lithium fluoride ceramic target material, wherein the lithium fluoride ceramic target material is used in the field of lithium-ion batteries or optical materials; the lithium fluoride ceramic target material is prepared according to the lithium fluoride ceramic target material described in the second aspect, or according to the preparation method of the lithium fluoride ceramic target material described in the first aspect.

[0042] The lithium fluoride ceramic target material prepared by the present invention has high density, which greatly improves the uniformity and efficiency of coating during the use of the target material, and enables it to be applied in the fields of lithium ion batteries and optical materials to function stably and efficiently.

[0043] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects:

[0045] (1) The present invention can obtain a high-density lithium fluoride ceramic target by adopting a sintering method combining pressureless sintering and HIP post-treatment without introducing any sintering aids. The HIP post-treatment can remove defects such as pores in the grain boundary area of ​​the sintered body to obtain a high-density lithium fluoride ceramic target.

[0046] (2) The density of the lithium fluoride ceramic target prepared by the present invention is above 97.0%, which significantly improves the density of the lithium fluoride ceramic target, greatly improves the uniformity and efficiency of the coating during the use of the target, and enables it to play a stable and efficient role in the fields of lithium ion batteries and optical materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a cross-sectional SEM of the lithium fluoride ceramic target material of Example 1 of the present invention;

[0048] Figure 2 This is a cross-sectional SEM of the lithium fluoride ceramic target material of Example 2 of the present invention;

[0049] Figure 3 This is a cross-sectional SEM of the lithium fluoride ceramic target material of Example 3 of the present invention;

[0050] Figure 4 This is a cross-sectional SEM of the lithium fluoride ceramic target material of Example 4 of the present invention;

[0051] Figure 5 This is a cross-sectional SEM of the lithium fluoride ceramic target material of Comparative Example 1 of the present invention;

[0052] Figure 6 This is a cross-sectional SEM of the lithium fluoride ceramic target material of comparative example 2 of the present invention. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0054] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental preparation methods and technical means used were conventional preparation methods and means in the field.

[0055] Example 1

[0056] This embodiment provides a method for preparing a lithium fluoride ceramic target, the preparation method comprising the following steps:

[0057] The lithium fluoride was dried at 80°C for 8 hours, and then sieved to obtain lithium fluoride with an average particle size of 60 nm;

[0058] The precursor is obtained by uniformly mixing lithium fluoride with an average particle size of 60 nm and a PVA solution with a concentration of 2.5 wt %, wherein the mass fraction of the binder solution in the precursor is 3 wt %; the precursor is molded or dry pressed, and then cold isostatically pressed at 150 MPa for 35 min to obtain a green blank;

[0059] The green blank was heated to 600°C at a heating rate of 5°C / min and pressurelessly sintered for 3 hours to obtain a sintered body. The sintered body was post-treated by HIP at 650°C and 50 MPa for 3 hours to obtain a lithium fluoride ceramic target.

[0060] The cross-sectional SEM image of the prepared lithium fluoride ceramic target is as follows: Figure 1 shown.

[0061] Example 2

[0062] This embodiment provides a method for preparing a lithium fluoride ceramic target, the preparation method comprising the following steps:

[0063] The lithium fluoride was dried at 60°C for 18 hours, and then sieved to obtain lithium fluoride with an average particle size of 50 nm;

[0064] The precursor is obtained by uniformly mixing lithium fluoride with an average particle size of 50 nm and a PVA solution with a concentration of 1 wt %, wherein the mass fraction of the binder solution in the precursor is 5 wt %; the precursor is molded or dry pressed, and then cold isostatically pressed at 50 MPa for 60 min to obtain a green blank;

[0065] The green blank was heated to 650°C at a heating rate of 1°C / min and pressurelessly sintered for 3 hours to obtain a sintered body. The sintered body was post-treated by HIP at 700°C and 80 MPa for 5 hours to obtain a lithium fluoride ceramic target.

[0066] The cross-sectional SEM image of the prepared lithium fluoride ceramic target is as follows: Figure 2 shown.

[0067] Example 3

[0068] This embodiment provides a method for preparing a lithium fluoride ceramic target, the preparation method comprising the following steps:

[0069] The lithium fluoride was dried at 90°C for 5 hours, and then sieved to obtain lithium fluoride with an average particle size of 100 nm;

[0070] The precursor is obtained by uniformly mixing lithium fluoride with an average particle size of 100 nm and a PVA solution with a concentration of 5 wt %, wherein the mass fraction of the binder solution in the precursor is 1 wt %; the precursor is molded or dry pressed, and then cold isostatically pressed at 250 MPa for 30 minutes to obtain a green blank;

[0071] The green blank was heated to 700°C at a heating rate of 10°C / min and pressurelessly sintered for 1 hour to obtain a sintered body. The sintered body was post-treated by HIP at 750°C and 60 MPa for 1 hour to obtain a lithium fluoride ceramic target.

[0072] The cross-sectional SEM image of the prepared lithium fluoride ceramic target is as follows: Figure 3 shown.

[0073] Example 4

[0074] This embodiment provides a method for preparing a lithium fluoride ceramic target, which is different from Embodiment 1 only in that lithium fluoride having an average particle size of 300 nm is obtained after sieving.

[0075] The cross-sectional SEM image of the prepared lithium fluoride ceramic target is as follows: Figure 4 shown.

[0076] Example 5

[0077] This embodiment provides a method for preparing a lithium fluoride ceramic target, which is different from Embodiment 1 only in that the HIP sintering temperature is set at 550°C.

[0078] Example 6

[0079] This embodiment provides a method for preparing a lithium fluoride ceramic target, which is different from Embodiment 1 only in that the temperature of the HIP post-treatment is 800°C.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing a lithium fluoride ceramic target, which is different from Example 1 only in that no HIP post-treatment is performed.

[0082] The cross-sectional SEM image of the prepared lithium fluoride ceramic target is as follows: Figure 5 As shown, it can be seen from the figure that there are a large number of pores.

[0083] Comparative Example 2

[0084] This comparative example provides a method for preparing a lithium fluoride ceramic target, which is different from Example 1 only in that the pressureless sintering is replaced by hot pressing sintering, and the pressure of the hot pressing sintering is 30 MPa.

[0085] The cross-sectional SEM image of the prepared lithium fluoride ceramic target is as follows: Figure 6 shown.

[0086] Test method: The relative density of the lithium fluoride ceramic targets prepared in Examples 1 to 6 and Comparative Examples 1 to 2 was determined by the Archimedean drainage method. The results are shown in Table 1 below.

[0087] Table 1

[0088] Density / % Example 1 97.2 Example 2 97.9 Example 3 98.3 Example 4 92.1 Example 5 90.2 Example 6 95.5 Comparative Example 1 88 Comparative Example 2 96.6

[0089] The test results show that:

[0090] (1) It can be seen from Examples 1 to 3 that the present invention can obtain a high-density lithium fluoride ceramic target by adopting a sintering method combining pressureless sintering with HIP post-treatment. The HIP post-treatment can remove defects such as pores in the grain boundary region of the sintered body to obtain a high-density lithium fluoride ceramic target. The density of the prepared lithium fluoride ceramic target is above 97.0%.

[0091] (2) By comparing Example 1 with Example 4, it can be seen that the present invention further controls the average particle size of the raw material lithium fluoride to 50nm-100nm, thereby obtaining a uniform and high-density lithium fluoride ceramic target. If a lithium fluoride material with an average particle size higher than 100nm is selected, the large-particle lithium fluoride material is not easy to form a dense material during pressureless sintering.

[0092] (3) By comparing Example 1 with Example 5-Example 6, it can be seen that the present invention further controls the temperature of HIP post-treatment to 600°C-750°C. The temperature of HIP post-treatment will affect the density of lithium fluoride ceramic target. The melting point of lithium fluoride is 845°C. If the temperature of HIP post-treatment is too high, the cost of equipment maintenance and replacement will increase; if the temperature of HIP post-treatment is too low, it is difficult to effectively eliminate pores and defects under low-temperature sintering conditions.

[0093] (4) It can be seen from Example 1 and Comparative Example 1 that if HIP post-treatment is not performed, the density of the prepared lithium fluoride ceramic target is only 88%, and the technical effect of improving the density of the lithium fluoride ceramic target cannot be achieved.

[0094] (5) It can be seen from Example 1 and Comparative Example 2 that by replacing pressureless sintering with hot pressing sintering, the density of the lithium fluoride ceramic target prepared is not much different from that of the hot pressing sintering method. However, the hot pressing sintering method has higher requirements on equipment and the process is more complicated. At the same time, the use of graphite molds during the sintering process causes carburization, which is not as simple as the preparation method of the present invention and has lower cost.

[0095] In summary, the present invention can obtain a high-density lithium fluoride ceramic target by adopting a sintering method combining pressureless sintering and HIP post-treatment without introducing any sintering aids. The HIP post-treatment can remove defects such as pores in the grain boundary area of ​​the sintered body to obtain a high-density lithium fluoride ceramic target. The density of the prepared lithium fluoride ceramic target is above 97.0%.

[0096] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium fluoride ceramic target, characterized in that: The preparation method comprises the following steps: The lithium fluoride and the binder solution are uniformly mixed to obtain a precursor, the precursor is molded or dry pressed, and then cold isostatically pressed to obtain a green blank; the green blank is pressurelessly sintered to obtain a sintered body, and the sintered body is post-treated with HIP to obtain a lithium fluoride ceramic target.

2. The preparation method according to claim 1, characterized in that: The temperature of the HIP post-treatment is 600°C-750°C; Preferably, the pressure of the HIP post-treatment is 70MPa-100MPa; Preferably, the HIP post-treatment time is 1 h-5 h.

3. The preparation method according to claim 1 or 2, characterized in that: The lithium fluoride is dried and sieved before mixing; Preferably, the drying temperature is 50°C-90°C; Preferably, the drying time is 2h-20h; Preferably, the average particle size of the lithium fluoride obtained after the screening treatment is 50nm-100nm.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The concentration of the binder solution is 1wt%-5wt%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The binder solution includes PVA solution or ethanol; Preferably, the mass fraction of the binder solution to the precursor is 0.5wt%-5wt%.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The cold isostatic pressing pressure is 50MPa-250MPa; Preferably, the cold isostatic pressing time is 30 min-60 min.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the pressureless sintering is 500°C-700°C; Preferably, the heating rate of the pressureless sintering is 1°C / min-10°C / min; Preferably, the pressureless sintering time is 1 h-5 h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Drying the lithium fluoride at 50°C-90°C for 2h-20h, and then sieving to obtain lithium fluoride with an average particle size of 50nm-100nm; The precursor is obtained by uniformly mixing lithium fluoride with an average particle size of 50nm-100nm and a PVA solution with a concentration of 1wt%-5wt%, wherein the mass fraction of the binder solution in the precursor is 0.5wt%-5wt%; the precursor is molded or dry pressed, and then cold isostatically pressed at 50MPa-250MPa for 30min-60min to obtain a green blank; The green blank is heated to 500-700°C at a heating rate of 1°C / min-10°C / min and pressurelessly sintered for 1h-5h to obtain a sintered body. The sintered body is post-treated by HIP at 600-750°C and 70MPa-100MPa for 1h-5h to obtain a lithium fluoride ceramic target with a density of 97%-99%.

9. A lithium fluoride ceramic target, characterized in that: The lithium fluoride ceramic target is prepared according to the method for preparing a lithium fluoride ceramic target according to any one of claims 1 to 8, and the density of the lithium fluoride ceramic target is 97%-99%.

10. A use of a lithium fluoride ceramic target, characterized in that: The lithium fluoride ceramic target is used in the field of lithium ion batteries or optical materials; The lithium fluoride ceramic target is the lithium fluoride ceramic target material according to claim 9, or a lithium fluoride ceramic target prepared according to the preparation method of the lithium fluoride ceramic target material according to any one of claims 1-8.

Citation Information

Patent Citations

  • Magnesium fluoride composite ceramic and preparation method thereof

    CN115872746A

  • Molybdenum tantalum oxide target material and preparation method and application thereof

    CN116332645A

  • Magnesium aluminate spinel transparent ceramic with high optical quality and preparation method thereof

    CN117658617A

Cited By

  • Lithium fluoride evaporation material as well as preparation method and application thereof

    CN120794631A